Lymphatic endothelial cells - key players in regulation of tolerance and immunity - Tewalt, Eric; Cohen, Jarish; Rouhani, Sherin; Engelhard, Victor (Frontiers in Immunology, 2012)
The lymphatic vasculature provides routes for dendritic cell and lymphocyte migration into and out of lymph nodes. Lymphatic endothelial cells (LEC) control these processes by expression of CCL21, sphingosine-1-phosphate and adhesion molecules. LEC express MHC-I and MHC-II, but not costimulatory molecules, and present antigen on MHC-I via both direct and cross presentation. Whether LEC present to CD4 T cells on MHC-II is unknown. Interestingly, LEC express antigens otherwise restricted to a small number of peripheral tissues in an Aire independent manner. Direct presentation of peripheral tissue antigens (PTA) to CD8 T cells results in abortive proliferation and deletion, due to both a lack of costimulation and active PD-L1 engagement. Autoimmunity develops when deletion is subverted, suggesting that LEC presentation of PTA could lead to human disease if PD-1 signaling were impaired by genetic polymorphisms, or aberrant costimulation occurred during inflammation. The expression of additional inhibitory molecules, which are not involved in LEC-mediated deletion, suggests that LEC may have additional immunoregulatory roles. LEC express receptors for several immunomodulatory molecules whose engagement alters their phenotype and function. In this review we describe the role of LEC in distinct anatomical locations in controlling immune cell trafficking, as well as their emerging role in the regulation of T cell tolerance and immunity.